To the tome of murder - Elliott, Lauren (Elliott, Lauren. Beyond the Page bookstore mystery., 2021)
When she stumbles upon the dead body of her cousin's boyfriend, bookshop owner Addie Greyborne reluctantly realizes she may be the only person to solve this grisly crime as she goes up against a dangerously well-read culprit.